THE EFFECT OF RECIPROCAL TEACHING TECHNIQUE TOWARDS STUDENTS READING COMPREHENSION OF ELEVENTH GRADE AT SMAN 1 KOTO KAMPAR HULU - Murti, Risna; Asilestari, Putri; Marleni, Lusi (TELL - US JOURNAL, 2023)
This study sought to investigate whether or not there was a significant difference in reading comprehension between students who were taught utilizing reciprocal teaching strategies and those who were not, as well as whether there was a significant effect of applying these strategies on reading comprehension. In September and October 2022, Senior High School 1 in Kampar Hulu was the site of the study. The Senior High School 1 Koto Kampar Hulu population for this study was made up entirely of eleventh graders. In class XI 1, the researcher utilized the reciprocal teaching technique as the experimental class, while in class XI 2, the researcher used the traditional strategy as the control class. A quantitative and experimental method was adopted in this study. Pretest and posttest were not equal in the study's quasi-experimental approach. Pre-test and post-test tests were used as study instruments to gather the data. The independent t-test and paired sample t-test statistic techniques from SPSS 22 were used to analyse and evaluate the data. The independent t-test calculation using the test results in both groups' posttest scores revealed that the significant value was greater than the level of significance (0,361 > 0,05). It demonstrated that the experimental and control groups' differences were indeed substantial. Additionally, the paired t-test calculation revealed the paired sample t-test result (-12,805 0,05), which indicated that adopting the reciprocal teaching strategy had a substantial impact on students' reading comprehension